2020
DOI: 10.1080/09168451.2020.1756733
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome alterations in HepG2 cells induced by shRNA knockdown and overexpression of TMEM2 gene

Abstract: Transmembrane 2 (TMEM2) gene inhibits chronic hepatitis-B virus (HBV) infection, while the underlying molecular mechanisms remain unknown. Transcriptome alterations in HepG2 cells following TMEM2 overexpression or silencing by shRNA were analyzed by next-generation sequencing. Both overexpression and knockdown of the TMEM2 gene caused wide-spread changes in gene expression in HepG2 cells. Differentially expressed genes caused by altered TMEM2 gene expression were associated with multiple biological processes l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, the activation of SYK also can be positively regulated by CD81, a member of the tetraspanin protein family, which promotes the development of hepatocellular carcinomas ( Figure 2 F). In recent years, some studies also indicated that SYK joins in the regulation of PI3K/Akt signaling pathway, which hold a key role in CX3CL1-induced platelet migration as well as cell apoptosis in human hepatocellular carcinomas [ 63 , 64 ]. Totally, the accurate position of SYK in hepatocellular carcinomas is still in controversial although some SYK inhibitors have showed the therapeutic effect against human hepatocarcinogenesis.…”
Section: The Relationship Between Syk and Different Liver Diseasesmentioning
confidence: 99%
“…In addition, the activation of SYK also can be positively regulated by CD81, a member of the tetraspanin protein family, which promotes the development of hepatocellular carcinomas ( Figure 2 F). In recent years, some studies also indicated that SYK joins in the regulation of PI3K/Akt signaling pathway, which hold a key role in CX3CL1-induced platelet migration as well as cell apoptosis in human hepatocellular carcinomas [ 63 , 64 ]. Totally, the accurate position of SYK in hepatocellular carcinomas is still in controversial although some SYK inhibitors have showed the therapeutic effect against human hepatocarcinogenesis.…”
Section: The Relationship Between Syk and Different Liver Diseasesmentioning
confidence: 99%
“…Growing evidence suggests that PI3K/AKT signaling directly or indirectly regulates important epigenetic modifications and is involved in the PI3K cascade-related tumorigenicity in cancer [ 20 ]. HOTAIR and SYK have been revealed to be the regulators of the PI3K/AKT pathway in adenocarcinoma of esophagogastric junction and HepG2 cells [ 21 , 22 ]. Therefore, the effect of the HOTAIR/miR-6888-3p/SYK axis on the PI3K/AKT pathway warrants further study.…”
Section: Introductionmentioning
confidence: 99%